A Comparison of Chemical Profiles of Callus, Plant and Agarwood Extracts of Gyrinops walla using Thin Layer Chromatography - Selvaskanthan, S.; Kaushalya, D.B.R.; Pushpakumara, D.K.N.G.; Jayasinghe, L.; Eeswara, J.P. (My University, 2020)
Agarwood produced by Gyrinops walla Gaertner, an endemic plant species of Sri Lanka, arguably the costliest wood, is used as a major constituent in cosmetic industries. Application of plant cell culture technique serves as the best alternative for the production of fragrance compounds of G. walla while ensuring the sustainability of the species. Using the advantages of plant cell culture and Thin Layer Chromatography (TLC), a preliminary study was carried out to compare the phytochemical constituents of callus and plant extracts (i.e stem, leaves, bark and agarwood) of G. walla. Different callus lines were developed on MS and modified MS media with reduced level of NH4NO3, supplemented with different combinations and concentrations of plant growth regulators and multiplied. Freeze dried samples were extracted with hexane, ethyl acetate and methanol and run on a TLC plate under different eluting solvent systems. A higher number of TLC spots were observed in the ethyl acetate extracts of all samples, under 15 percent methanol: chloroform solvent system. Based on TLC chemical profiles of all callus lines, MS media added with 1.0 mg/L BAP, 0.5 mg/L kinetin and 0.1 mg/L 2,4-D and ½ MS contained 1.0 mg/L BAP and 0.1 mg/L 2,4-D were selected as best lines. The extracts of the selected two callus lines matched with the fingerprint profiles of best plant samples i.e stem, bark and agarwood. Compounds present in the extracts of callus samples, plant samples and agarwood, appearing at Rf=0.56, 0.74 and 0.78, could be used as possible markers for G. walla. The chromatography profiling by TLC has proven the presence of similar phytochemical constituents in callus, plant samples and agarwood. Therefore, it can be concluded that plant cell culture technique guarantees the possibility to produce same compounds that are present in plant and agarwood of G. walla.
Keywords: Agarwood; Callus; Gyrinops walla; Plant growth regulators; Thin layer chromatography